The Silence Speaks, but We Do Not Listen: Synonymous c.1824C>T Gene Variant in the Last Exon of the Prothrombin Gene as a New Prothrombotic Risk Factor. (10th February 2020) - Pruner, Iva; Farm, Maria; Tomic, Branko; Gvozdenov, Maja; Kovac, Mirjana; Miljic, Predrag; Soutari, Nida Mahmoud Hourani; Antovic, Aleksandra; Radojkovic, Dragica; Antovic, Jovan; Djordjevic, Valentina
Abstract: Background: Thrombosis is a major global disease burden with almost 60% of cases related to underlying heredity and most cases still idiopathic. Synonymous single nucleotide polymorphisms (sSNPs) are considered silent and phenotypically neutral. Our previous study revealed a novel synonymous FII c.1824C>T variant as a potential risk factor for pregnancy loss, but it has not yet been associated with thrombotic diseases. Methods: To determine the frequency of the FII c.1824C>T variant we have sequenced patients' DNA. Prothrombin RNA expression was measured by quantitative PCR. Functional analyses included routine hemostasis tests, western blotting and ELISA to determine prothrombin levels in plasma, and global hemostasis assays for thrombin and fibrin generation in carriers of the FII c.1824C>T variant. Scanning electron microscopy was used to examine the structure of fibrin clots. Results: Frequency of the FII c.1824C>T variant was significantly increased in patients with venous thromboembolism and cerebrovascular insult. Examination in vitro demonstrated increased expression of prothrombin mRNA in FII c.1824T transfected cells. Our ex vivo study of FII c.1824C>T carriers showed that the presence of this variant was associated with hyperprothrombinemia, hypofibrinolysis, and formation of densely packed fibrin clots resistant to fibrinolysis. Conclusion: Our data indicate that FII c.1824C>T, although a synonymous variant, leads to the development of a prothrombotic phenotype and could represent a new prothrombotic risk factor. As a silent variant, FII c.1824C>T would probably be overlooked during genetic screening, and our results show that it could not be detected in routine laboratory tests.